Analisis Teoritik Atas Tulisan Geertz Tentang Kyai Jawa Sebagai Cultural Broker - Moch. Muwaffiqillah (Indonesian Journal of Humanities and Social Sciences, 2023)
This journal article aims to conduct a theoretical analysis of Geertz's article entitled "Javanese Kyai as Cultural Broker." Geertz's writing became one of the important contributions in anthropological studies on religion and culture in Indonesia. Geertz explains the role of the Javanese kyai as a cultural broker in Javanese society. The theoretical analysis in this article includes a study of the main concepts introduced by Geertz, such as kyai, culture, and cultural brokers. Through a theoretical approach, this article investigates these concepts with reference to anthropological theories and other relevant studies. The aim was to gain a deeper understanding of the role of Javanese kyai as cultural brokers in Javanese society. The study found that Kyai as a cultural broker acts as a mediator between different cultural groups, facilitating understanding, dialogue, and exchange between Javanese community groups and foreigners, such as the Japanese and Western cultures brought by modernists and the Dutch. The role of Kyai as a cultural broker has changed in line with changes in Indonesia's sociocultural and political systems. To continue to exist, Kyai needs to combine religious and secular knowledge and be involved in the NU political party, which has a coordinated organizational structure from the central to the branch level.